ANALISIS NILAI PROFIL PELAJAR PANCASILA PADA CERITA PENDEK DALAM BUKU BAHASA INDONESIA LIHAT SEKITAR KELAS IV SDN 2 PANGENREJO - Raysita Cahya Anggraeni; Arun Ratnaningsih; Muflikhul Khaq (LPPM STKIP Bina Bangsa Meulaboh, 2024)
This research aims to analyze the profile value of Pancasila students in short stories in the Indonesian language book Look Around for class IV at SD N 2 Pangenrejo. The type of research used is qualitative research. The data collection techniques used in this research were observation, interviews, documentation and data cards. The instrument of this research is a data card. The data analysis techniques used were data collection, data reduction, data presentation and data verification. The research results showed that there were 28 Pancasila student profile character values ​​in short stories. The short stories with the most Pancasila student profile scores are